RASIONALISASI POS HIDROLOGI PADA SATUAN WILAYAH SUNGAI (SWS) LAMBUNU – BUOL DENGAN METODE KAGAN - Sutapa, I Wayan (MEKTEK, 2009)
The aim of this research is to get post network of hydrology efficient, effective and can deputize a catchment area so that earn minimization of is expense of required for the operation and conservancy. Data the used is monthly rainfall during 10 years start from year 1997 till 2006. Method which is used in data analysis that is method of Kagan. Pursuant to result of Method analysis of Kagan for the SWS of Lambunu-Buol with amount of existing rain post in this time amount to 13 posts with mistake of calculation according to result of analysis 2,814 % obtained by distance between post 45,199 km, amountly have answered the demand of but spreading of rain post not yet fulfilled what required by Kagan, so that require to be conducted by post reposition. Existing posts will be reposition are Station of Tada, Kayu Agung, Ongka, Lalos and Air Terang